2010
DOI: 10.1371/journal.ppat.1000916
|View full text |Cite
|
Sign up to set email alerts
|

VEGF Promotes Malaria-Associated Acute Lung Injury in Mice

Abstract: The spectrum of the clinical presentation and severity of malaria infections is broad, ranging from uncomplicated febrile illness to severe forms of disease such as cerebral malaria (CM), acute lung injury (ALI), acute respiratory distress syndrome (ARDS), pregnancy-associated malaria (PAM) or severe anemia (SA). Rodent models that mimic human CM, PAM and SA syndromes have been established. Here, we show that DBA/2 mice infected with P. berghei ANKA constitute a new model for malaria-associated ALI. Up to 60% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
144
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(165 citation statements)
references
References 45 publications
12
144
0
9
Order By: Relevance
“…In vivo analyses showed no brain sequestration of mononuclear cells, no vascular leak, no hemorrhage, and no inflammation in the absence of IL-12Rb2, which were evident in PbA-infected WT mice. In contrast, the absence of IL-12Rb2 did not affect PbA-induced pulmonary microvascular damage, thus confirming the different pathophysiology of PbA-induced ECM and lung pathology (10,38,39). Thus, we demonstrated that PbA-induced brain microvascular damage and inflammation are mainly IL-12Rb2 dependent, whereas PbAinduced lung microvascular damage, edema, and alveolitis are IL-12Rb2 independent.…”
Section: Discussionsupporting
confidence: 75%
“…In vivo analyses showed no brain sequestration of mononuclear cells, no vascular leak, no hemorrhage, and no inflammation in the absence of IL-12Rb2, which were evident in PbA-infected WT mice. In contrast, the absence of IL-12Rb2 did not affect PbA-induced pulmonary microvascular damage, thus confirming the different pathophysiology of PbA-induced ECM and lung pathology (10,38,39). Thus, we demonstrated that PbA-induced brain microvascular damage and inflammation are mainly IL-12Rb2 dependent, whereas PbAinduced lung microvascular damage, edema, and alveolitis are IL-12Rb2 independent.…”
Section: Discussionsupporting
confidence: 75%
“…Studies by Shiloh et al (45) and Kumar et al (41) revealed that in addition to HO-1, CO can induce the M. tuberculosis dormancy regulon as well. Another study observed that treatment of mice with exogenous CO increases Plasmodium liver load (26), but fully prevents cerebral malaria and malaria-associated acute lung injury incidence in mice (27,77).…”
Section: Discussionmentioning
confidence: 99%
“…Control experiments were performed to determine whether the intracranial injection procedure and the administration of nilvadipine could affect the permeability of the BBB. Vascular permeability/ BBB leakage was evaluated by measuring the extravasation of the Evans blue dye in the brain as described previously (25,26). Briefly, B6/SJL F1 mice were intraperitoneally injected with 100 μL of 50% DMSO/PBS (vehicle), with 2 mg/kg of nilvadipine or were injected intracranially as described above with 3 μL of vehicle, with 3 nmol of Aβ or went untreated (control mice).…”
Section: Effects Of Dihydropyridines On Aβ Clearance Across the Bbb Imentioning
confidence: 99%
“…permeability (25,26). The cold injury procedure which induces a rapid breakdown of the BBB (31) was used as a positive control and lead to a significant extravasation of the Evans blue dye in the brain (see Figure 7).…”
Section: In Vivo Effects Of Antihypertensive Dhps In Transgenic Mousementioning
confidence: 99%